Kedai Kopi Kontemporer: Tinjauan Kritis Ruang Publik Habermas Di Kedai Kopi Masa Moeda Medan - Fajar Nur Bahri; Muzakkir; Jufri Naldo (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This research analyzes Kedai Kopi Masa Moeda Medan as a public sphere from the perspective of Jürgen Habermas's theory and Islamic tradition. The proliferation of contemporary coffee shops in Indonesia raises questions about their function as arenas for critical democratic discourse or merely spaces of consumerism. The research employs a qualitative approach with participatory observation and literature study to analyze physical characteristics, social activities, interaction patterns, and the quality of discourse. Findings reveal that Kedai Kopi Masa Moeda has ambivalent characteristics: discourses on political, economic, and social issues reflect elements of a critical public sphere, yet the space is dominated by entertainment and consumption activities with economic barriers excluding low-income groups and persons with disabilities. The research concludes that the coffee shop only partially fulfills Habermas's public sphere criteria, reflecting the refeudalization of public space from deliberative arena to consumption sphere. Comparative dialogue reveals convergence between Habermas and Islam in emphasizing rational discussion and common interest, yet divergence in secular versus religious orientation and the dimension of Islamic hospitality not accommodated in the Habermasian framework. The implication calls for a contextual Islamic public sphere concept for Indonesian Muslim society.